The Role of Sports in Enhancing Social Skills Among Elementary Students - Mudayat Mudayat (Performa, 2025)
Social skills are a key component of a child’s development both personally and academically, as they enable them to communicate, cooperate, and resolve conflicts. The advancement of these skills through education has differing approaches, but participation in sports is widely accepted to promote social relations and collaboration. Nevertheless, there is little scientific research on the degree to which organised sports activities facilitate social skills development in children. Therefore, the purpose of this study was to evaluate the impact of sports participation on the social skills of elementary students by measuring their communication, teamwork, conflict resolution, and leadership skills. A quasi-experimental approach was implemented with 70 elementary school students, half of whom participated in structured sports activities while the other half did not. Group 1 was the experimental class that actively participated in the organised sports while group 2 served as the control class. Information was gathered through self-report questionnaires, observational checklists, and peer interaction evaluation. To identify significant differences between two sets of measurements made before and after interventions, a paired t-test was performed. The results showed that learners in the experimental group had greater improvements in communication (+1.2 points, p = 0.003), teamwork (+1.5 points, p = 0.002), and conflict resolution (+1.1 points, p = 0.004) than the control group which had no improvements (p > 0.05). The observational data also revealed that the sports participants showed higher involvement, leadership, and teamwork. These results imply that organised sports can be used as an important tool to enhance social skills among elementary school students.